Lead compound discovery using pharmacophore-based models of small-molecule metabolites from human blood as inhibitor cellular entry of SARS-CoV-2 - Ellin Febrina; Aiyi Asnawi (GarVal Editorial Ltda., 2023)
Context: The development of emerging viral diseases like SARS-CoV-2 has underlined the critical need for new antiviral medicines. Many of the discovered inhibitors have off-target effects or toxicity issues, but no single lead chemical has been found as a powerful SARS-CoV-2 inhibitor. Small-molecule metabolites from human blood, for example, have been demonstrated to exhibit biological action, such as anti-inflammatory or antiviral properties, but have not been reported as pharmacophore-based drug discovery models. Aims: To evaluate the feasibility of employing pharmacophore models of small-molecule metabolites taken from human blood as a lead discovery method for SARS-CoV-2 inhibitors. Methods: A total of six small-molecule metabolites from human blood were utilized to construct a pharmacophore model, which was then used to simulate the interaction's stability for the top two-rank ligands with the best interactions using molecular docking and molecular dynamics. Results: The area under the curve value of the pharmacophore model created using the best pairwise alignments approach was 0.576, indicating that it is suitably validated as a model. The pharmacophore model was utilized for virtual screening, followed by molecular docking, yielding 75 hits. An investigation of the molecular dynamics of two top-rank hits (ZINC000085567845 and ZINC000085567870) revealed a stable interaction with the SARS-CoV-2 spike protein. Conclusions: Finally, the pharmacophore model developed was capable of discovering lead compounds with the potential as SARS-CoV-2 spike protein inhibitors.